Contrasting impact of invasive alien sport fish in the Cape Floristic Region : a focus on Micropterus dolomieu - Barrow, Stuart Bruce (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScConsEcol)--Stellenbosch University, 2014.